Digitalization in the Service of Preserving the Cultural Heritage of the Metropolitan Library of Zagreb’s Archbishopric, Croatia - Domazet, Emilia; Vržina, Goran (Bobcatsss, 2023)
Metropolitan Library of Zagreb’s Archbishopric is a jewel among Croatian libraries with its valuables. The Library presents a treasure of the written word and is highly cherished in our cultural and national history. Development and prevalence of ICT in all segments of everyday life resulted in progress of social sciences and production of new knowledge platforms. The digitalization enables access, preservation and possibility of multiple uses of materials by libraries, archives and museums. In the Library there are many manuscripts (codices), incunabula, books printed from 16th to 20th century and occasional publications. Valvasor’s graphic collection is a part of a corpus that provides insight into graphic production from late 15th until 17th century. Digitalization of the collection improves permanent protection and online availability of digital content. The aim of this paper is to introduce this valuable Metropolitan Library collection to the entire professional community by applying new technologies. This paper will highlight the cooperation between institutions and experts of different profiles, depending on the type of material that is situated in the Library itself. Its unique goal is the preservation of cultural heritage which represents national identity. Certain number of units has been digitized with the non-invasive Low Light digitization, which will also be presented in this paper. Using the non-invasive Low Light digitalization, the criterion how to carry out any digitalization has been elevated to higher standards, and it simplified the creation of quality documentation consistent with library, archival and especially museum informational standards. This system was created with an idea that it should uncompromisingly preserve historical original from any physical and chemical degradation. That makes the system extremely suitable for any type of digitalization, especially digitalization of originals before restoration. Using this system, it is possible to preserve important yet interesting “part” of the original before restoration